Community Innovation Fund from implementation to scaling out of climate-smart agriculture practices - Tam Thi Le; Simelton, Elisabeth; Hai Van Le (2018)
A Community Innovation Fund (CIF) is a simple kick-start fund to support farmer interest groups who have limited access to formal financial services for implementing climate-smart agriculture (CSA) practices. A CIF can be implemented as sole fund or as co-investment to community savings and loans groups. In this publication, a step-by-step guide for facilitating a CIF in a community, based on experiences from My Loi Climate-Smart Village (CSV), was provided. My Loi is one of three CCAFS CSVs in Vietnam, where participatory CSA practices are being tested and adopted. In My Loi, it took about 12 months from the initial CIF introduction before farmers were able to independently regulate their own savings and loans distributions.